2022
DOI: 10.3390/healthcare10071212
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Type of Delivery on Female Postpartum Sexual Functioning: A Systematic Review

Abstract: Female sexual function could be considered as multifactorial. Specific physiological structures and hormonal fluctuations postpartum, along with the psychological adjustment of women, could result in altered sexual function. The primary aim of this review was to systematically appraise the existing data on the effect of mode of delivery on female sexual function. This review was designed based on the PRISMA statement guidelines. An extensive literature search was performed in the Pubmed, Scopus, and PsycInfo d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 43 publications
3
5
0
Order By: Relevance
“…However, there is controversy in the literature regarding the association between the type of birth and the incidence of sexual dysfunction, with the majority finding results in line with those identified in our study. 23,24 Pelvic floor disorders were associated with a higher incidence of sexual dysfunction in our results, in agreement with Zhuo et al 11 or in the literature review carried out by Verbeek and Hayward 10 and in line with other authors. 9 Although other authors, such as Li-Yun-Fong et al, 25 concluded that women with pelvic floor disorders had a large burden of sexual dysfunction, which seems to be mediated by factors may lead to pain, loss of urine or feces, as well as the descent and even exit through the vagina of the pelvic organs.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…However, there is controversy in the literature regarding the association between the type of birth and the incidence of sexual dysfunction, with the majority finding results in line with those identified in our study. 23,24 Pelvic floor disorders were associated with a higher incidence of sexual dysfunction in our results, in agreement with Zhuo et al 11 or in the literature review carried out by Verbeek and Hayward 10 and in line with other authors. 9 Although other authors, such as Li-Yun-Fong et al, 25 concluded that women with pelvic floor disorders had a large burden of sexual dysfunction, which seems to be mediated by factors may lead to pain, loss of urine or feces, as well as the descent and even exit through the vagina of the pelvic organs.…”
Section: Discussionsupporting
confidence: 93%
“…Having had vaginal births has not been identified as a factor associated with the presence of sexual dysfunction. However, there is controversy in the literature regarding the association between the type of birth and the incidence of sexual dysfunction, with the majority finding results in line with those identified in our study 23,24 …”
Section: Discussionsupporting
confidence: 89%
“…Many studies included in this review show that mode of birth is not associated with postpartum sexual functioning in the medium- and longer-term. This supports the findings of Nikolaidou in their systematic review, on the effect of mode of birth on sexual function in the short- and medium-term (up until 12 months postpartum) [ 36 ].…”
Section: Discussionsupporting
confidence: 89%
“…Systematic reviews on the association between mode of birth and postpartum sexual function have been undertaken in 2004, 2010, 2020 and 2022 [ 3 , 34 , 35 , 36 ]. Results from these systematic reviews varied: a review showed that caesarean section was protective of sexual function compared to vaginal birth [ 34 ], another showed a strong association between assisted vaginal birth and worse sexual function when compared to other modes of birth [ 35 ], whilst others showed no relationship between mode of birth and postpartum sexual function [ 3 , 36 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation